INFLUENCE OF SONICATION ASSISTED DISPERSION METHOD ON THE MECHANICAL AND ELECTRICAL PROPERTIES OF NYLON 66/NANO-COPPER NANOCOMPOSITE - Shueb, Mohammed Iqbal; Abd Manaf, Mohd Edeerozey; Ratnam, Chantara Thevy; Mohamad, Noraiham (2017)
Nylon 66 is a well known engineering polymer with excellent mechanical and thermal properties. However, its poor electrical conductivity restricts its application for conductive material. In this study, nano-copper particles are added into nylon 66 polymer matrix to enhance the electrical conductivity value of the nanocomposite. Sonication assisted dispersion method was used to achieve well dispersed nanomaterials through reasonable exfoliation of the nano-copper particles in the nylon 66 polymer. The impact of sonication on the mechanical performance and the electrical conductivity of nanocomposite were evaluated. The sonication was found to effectively reduce agglomeration of nano-coppers in nylon 66, and improved both mechanical performance and electrical conductivity of the nanocomposite. Irrespective of the nano-copper amount, nanocomposite with sonication-treated nano-copper consistently showed higher hardness and impact strength than nanocomposite without sonication. The electrical conductivity increased by two orders of magnitude from 10-15 to 10-13 for the nanocomposite added with sonication-treated nano-copper compared to that without sonication treatment.